2018
DOI: 10.1007/s11136-018-1931-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and assessment of health-related quality of life issues in patients with sporadic desmoid-type fibromatosis: a literature review and focus group study

Abstract: PurposeSporadic desmoid-type fibromatosis (DTF) is a rare, chronic, non-metastasising, disease of the soft tissues. It is characterised by local invasive and unpredictable growth behaviour and a high propensity of local recurrence after surgery thereby often having a great impact on health-related quality of life (HRQL). This study aims to review currently used HRQL measures and to asses HRQL issues among DTF patients.MethodsA mixed methods methodology was used consisting of (1) a systematic literature review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…In addition, they are susceptible to periods of anxiety from diagnosis and during treatment due to uncertainty about therapeutic options [ 67 , 68 ]. Recently there has been a greater interest in the subject, and it is reflected in the creation of different organizations such as The Desmoid Tumor Research Foundation in the United States and the creation of patient advocacy groups in various institutions and social media [ 69 , 70 ]. Many of the series presented in this review revealed that pain might be a common indication for patients undergoing active surveillance to shift to a more aggressive treatment strategy namely surgery, systemic treatment or radiotherapy; therefore, it is strongly encouraged to keep in mind that since it is a benign tumor, it would be reasonable to measure a symptom-free survival period instead of progression free survival.…”
Section: Quality Of Lifementioning
confidence: 99%
“…In addition, they are susceptible to periods of anxiety from diagnosis and during treatment due to uncertainty about therapeutic options [ 67 , 68 ]. Recently there has been a greater interest in the subject, and it is reflected in the creation of different organizations such as The Desmoid Tumor Research Foundation in the United States and the creation of patient advocacy groups in various institutions and social media [ 69 , 70 ]. Many of the series presented in this review revealed that pain might be a common indication for patients undergoing active surveillance to shift to a more aggressive treatment strategy namely surgery, systemic treatment or radiotherapy; therefore, it is strongly encouraged to keep in mind that since it is a benign tumor, it would be reasonable to measure a symptom-free survival period instead of progression free survival.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Health-related quality of life (HRQoL) provides information beyond traditional measures of efficacy in oncology such as overall survival and is increasingly used as an endpoint in clinical trials [10,11]. We previously performed a systematic literature review to evaluate which HRQoL measures were used in research to assess HRQoL in DTF [12]. Generic HRQoL measures (e.g., the cancer-specific core questionnaire from European Organisation for Research and Treatment of Cancer; the EORTC Quality of Life Core Questionnaire (EORTC QLQ-C30)) may not consider disease-specific issues in DTF patients.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no validated DTF-specific HRQoL tool, and this was illustrated by a systematic literature review published by our group [12,13]. In order to gain greater insight into the issues that patients with DTF experience in their daily lives, and to evaluate their experiences of healthcare including the supportive care system, we previously organised focus groups and semistructured interviews, in the United Kingdom (UK) and in the Netherlands (NL) [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to prospectively develop a novel regulatory and clinical trial endpoint to characterize the subjective experience in patients with DTs, an ultrarare cancer. Although a recent review indicated the need for a health‐related quality of life (HRQOL) tool for patients with DTs, an important step in the regulatory context is to ensure that the PRO measure is uniquely developed for DTs to complement existing HRQOL instruments such as the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30, the Patient‐Reported Outcomes Measurement Information System, and the MD Anderson Symptom Inventory, which are not specific to a disease or condition. We sought to develop a PRO tool that captures desmoid‐related symptoms and impacts in accordance with the 2009 guidance for industry from the US Food and Drug Administration (FDA): Patient‐Reported Outcome Measures: Use in Medical Product Development to Support Labeling…”
Section: Introductionmentioning
confidence: 99%